Organisational capacities and management of agricultural extension services In Nigeria: Current status - Davis, Kristin E.; Lion, K.; Arokoyo, Tunji (Academy of Science of South Africa, 2019)
Organisational capacity and management are critical elements of extension systems. This paper examines the organisational capacity and management of the Nigerian extension system. Content analysis of documents and artefacts, semi-structured interviews with key informants, and site visits were used to collect data. The paper looks at individual, organisational, and system-level capacities and management systems. The current ratio of extension agents to farmers is between 1:5000 and 1:10 000, with a total workforce of about 7000 public agents. A new initiative, the N-Power programme, is employing 100 000 young graduates in extension. Financing provided by state governments typically only covers the salaries of extension staff, meaning there is little operational budget for travel, communication, training, or field programmes. States thus struggle to hire and provide incentives for staff, and most continuing education and incentives take place in donor-funded projects or with federal funds. The extension system has good support from policies and strategies, as well as from research, education, and donor programmes. The paper confirms that capacity and management issues are critically important for well-functioning extension systems, and that there are many elements to get right, including continuing education, incentives, coordination, and operational budgets.